Ethyl oleate ozonide as an epoxidation tool of C60 and C70 fullerenes. Issue 3 (4th March 2017) - Ursini, Ornella; Cataldo, Franco
ABSTRACT: When dissolved in ethyl oleate secondary ozonide, both C60 and C70 fullerenes undergo a series of epoxidation reactions. The pseudofirst-order kinetic rate constants of this process were determined spectrophotometrically at various temperatures and the activation energy for C60 epoxidation through ethyl oleate ozonide was found at 25.9 kcal/mol. Furthermore, C60 was found more reactive than C70 with the ozonide. The kinetics rate constants of C60 epoxidation with ethyl oleate ozonide were compared with the C60 photo-oxidation and auto-oxidation determined in pure ethyl oleate. The epoxidation of fullerenes starts from the homolysis of the peroxide group of the 1, 2, 4-trioxolane ring of ethyl oleate secondary ozonide. Thus, it is suggested that fullerenes have a potential as decomposition agents of secondary ozonides in some technological applications.